2016
DOI: 10.21608/jpp.2016.45533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Application of Yeast on Yield and Seed Quality of Some Rice Cultivars

Abstract: and 2013 seasons to study the effect of 5 concentrations of dry yeast (Saccharomyces cervisia) i.e. 0, 2, 4, 6 and 8 g/L as foliar application at 25, 55 and 85 days after sowing on growth characters, yield and its components of Giza 178, Sakha 105 and Sakha 106 rice cultivars. The produced seeds obtained from the field experiment were investigated under Laboratory condition to study seed quality characters) seed, seedling vigor and its health) at Seed Technology Research Unit in Mansoura, Egypt. Results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Treating plants with various substances including A 3 , A 2 and A 4 produced about (16.25 and 23.03 %), (9.38 and 14.47 %) and (8.75 and 13.16 %) more seed yield than untreated plants (A 1 ) in 2017 and 2018 seasons, respectively. Dewedar and Ibrahim (2016) found that foliar application of dry yeast on rice gave the highest values of yield and yield components. The positive effect of yeast extract upon seed yield attributed to the early vigorous growth of sunflower plants (Tables 4 and 5) Results presented in Table (6) showed that spraying sunflower plants with some compounds caused significant promotion of seeds quality of sunflower, i.e., , oil yield, oil %and protein% particularly in yeast extract (A 3 ) treated plants to about (27.72 and 28.94 %), (10.11 and 4.75 %) and (13.79 and 12.29 %) above the control value during the two growing seasons, respectively.…”
Section: Effect Of Foliar Application Treatments (A)mentioning
confidence: 98%
“…Treating plants with various substances including A 3 , A 2 and A 4 produced about (16.25 and 23.03 %), (9.38 and 14.47 %) and (8.75 and 13.16 %) more seed yield than untreated plants (A 1 ) in 2017 and 2018 seasons, respectively. Dewedar and Ibrahim (2016) found that foliar application of dry yeast on rice gave the highest values of yield and yield components. The positive effect of yeast extract upon seed yield attributed to the early vigorous growth of sunflower plants (Tables 4 and 5) Results presented in Table (6) showed that spraying sunflower plants with some compounds caused significant promotion of seeds quality of sunflower, i.e., , oil yield, oil %and protein% particularly in yeast extract (A 3 ) treated plants to about (27.72 and 28.94 %), (10.11 and 4.75 %) and (13.79 and 12.29 %) above the control value during the two growing seasons, respectively.…”
Section: Effect Of Foliar Application Treatments (A)mentioning
confidence: 98%
“…On the other hand, yeast acts as biological stimulator to growth due to production of growth promoting substances, and has high ability to make active association with the non-leguminous crops such as rice, sugar beet and wheat [24,25]. Foliar spray using yeast (Saccharomyces cerevisiae) increased rice yield components, improved seed quality and decreased seed-borne fungi [24].…”
Section: Integrated Biofertilization Increased Wheat Yield Componentsmentioning
confidence: 99%
“…The yeast species Saccharomyces cerevisiae is an ecofriendly and natural biological stimulator for plant growth. Previous reports elucidated the high efficiency of yeast extract to increase plant growth, yield components and grains quality of different crops such faba bean [23], rice [24], sugar beet [25] and maize [26]. As a result, the development of biofertilizers using a combination of two or more microorganisms such as cyanobacteria-bacteria or bacteria-bacteria has been found to enhance wheat height, dry weight, and grains yield [16,17,21,27].…”
mentioning
confidence: 99%
“…Yeast (Saccharomyces cerevisiae) is a living organism (fungi) that contains many important nutrients for plants such as iron, calcium, magnesium, potassium, nitrogen, sodium, phosphorus, zinc and silicon (Table 2). It is rich in growth regulators such as gibberellins and oxins (De Wedar & Ibrahim, 2016). It was found that AYE increase vegetative growth such as plant height and leaf area (Ezz El-Din & Hendawy, 2010).…”
Section: Effect Of Micronutrients Application and Spraying Yeast Extract On Yieldmentioning
confidence: 99%